1909 Wash. Sess. Laws 973, An Act Relating to Crimes and Punishments and the Rights and Custody of Persons Accused or Convicted of Crime, and Repealing Certain Acts, ch. 249, ch. 7, §266, pts. 1-3 - (:unkn) unknown (My University, 1909)
Prohibited the setting of any trap, spring pistol, rifle, or other deadly weapon. Punishable by imprisonment for up to 1 year or a fine of up to $1,000. Further punishable by imprisonment for up to 20 years for non-fatal or fatal injuries resulting from the trap.
Keywords: TRAP GUNS